Edukasi Bahaya Narkoba Perspektif Hukum Pidana dan Maqashid Syariah - Basit Misbachul Fitri, Abd; Yusuf, M (Jurnal Bangun Abdimas, 2022)
- Educational assistance on the dangers of drugs in terms of criminal law and sharia maqashid really needs to be done among youth so that their knowledge and insight becomes wider and can become self-control in avoiding drug use, this activity targets a group of teenagers who are members of the Cold Youth Paguyuban (PPD) Ngronggot Nganjuk. In general, their knowledge about the dangers of drugs from a health perspective is understandable, however. knowledge and insight into the dangers of drugs from the perspective of criminal law and maqashid sharia are still many who do not understand. The expected result of this assistance is that the youth in the assisted target are more enthusiastic in their activities and are free from drugs and have a strong mentality in facing the challenges of the globalization era, because this is very necessary for the Cold youth community of Ngronggot village when hanging out with others in the community. The training method is carried out by means of discussion and interactive in conveying knowledge to training participants. Based on the results of the training, there was a large increase in knowledge obtained by partners with the acquisition of the average pretest score of 36.84%, while the average posttest result was 54.74%.